Effect of Sub-Zero Treatment on the Microstructure and Hardness of High-Chromium White Cast Iron [Efecto del Tratamiento Sub-Cero Sobre la Microestructura y Dureza de Fundiciones Blancas Alto Cromo] - Ordonez, S; Leiva-Illanes, R; Hernandez-Duran, E (Universidade Federal do Rio de Janeiro, 2018)
The effect of the sub-zero treatment temperature on the transformation of retained austenite to martensite in two high chromium white cast irons (ASTM A532 Class II Type B) was studied. The sub-zero treatment ap-plied to each alloy in the as cast condition was performed at -40, -65 and -180 ° C for 10 minutes; after the holding time was completed the samples were cooled to room temperature. The microstructure of the as cast condition was analyzed by optical microscopy (LOM) and scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) analysis was also performed with the aim to identify the microconstituents initially present in each alloy. The metallographic characterization of the specimens subjected to sub-zero treatment was performed by optical microscopy. Furthermore, Brinell hardness was measured in the as cast and sub-zero treated samples. The alloys studied have important differences in chemical composition, mainly in the molybdenum and cop- per content, which mainly determine its microstructure. The results showed an increase in the hardness of both alloys with decreasing treatment temperature; which is due to the fact that the amount of retained aus-tenite transformed to martensite increases as the martensite finish temperature (Mf) is reached. It was also observed that a higher molybdenum content produces a metastable austenitic matrix in the as cast samples. Furthermore, the effect of Mo and other alloying elements substantially stabilizes the austenite, obtaining low amounts of martensite after the sub-zero treatment, even at -180 ° C. © 2018, Universidade Federal do Rio de Janeiro. All rights reserved.